Negligência e abandono contra a pessoa idosa em Aracaju/SE (2018-2021) - Oliveira, Mary Nadja Aragão (2023)
The World Health Organization (WHO) defines violence against the elderly as a single or repeated act or omission, which may be intentional or unintentional, causing harm, suffering, or distress. It can occur internally or externally within the domestic environment, involving family members or individuals in a relationship with them. Neglect refers to the refusal or omission of due and necessary care by family or institutional caregivers. Therefore, this descriptive study aimed to analyze data on the neglect and abandonment of older adults in the municipality of Aracaju (SE) from 2018 to 2021. The universe consisted of cases reported in the System of Information on Notified Harm (SINAN) of the Ministry of Health (MS). This is a descriptive study. A total of 278 cases of violence were reported among people aged 60 years and older. Neglect/abandonment was the primary type of violence during the analyzed period (48.2%), followed by physical (26.6%), psychological/moral (10.4%), financial (8.1%), and other types of violence (5.7%). The results revealed the notification of 125 cases of neglect or abandonment of the elderly in Aracaju/SE, primarily affecting black women (58%) with incomplete primary education (14.4%). The main aggressors were sons and daughters (68%), siblings (14.4%), spouses (8%), others (15.2%), caregivers (2.4%), and strangers (1.6%). Repetition was observed in 61.6% of the cases, and self-inflicted injury occurred in 1.6%. The cases took place in their own residences (95.2%) and in commerce or services (2.4%). It is necessary to consider that intrafamily violence and ill-treatment need to be analyzed in the context of social and structural violence to which the elderly are exposed as an expression of social constructs regarding gender, old age, and intergenerational relations. It is essential to analyze changes in family arrangements and the role of women, who are often seen as the primary and/or exclusive caregivers. In this regard, it is reaffirmed that older women are at high risk due to the aging process. Violence is a public health problem, and its reporting allows victims to be referred to the appropriate authorities to ensure protection, break the cycle of violence, and secure their rights to life, health, and well-being, as well as to develop public policies for prevention and health promotion for this population. It is essential to reexamine commitments to the well-being of this population, both by the state and by society and the family, to ensure that the necessary care is provided to preserve the health of this population group.